2021
DOI: 10.52547/ijn.34.131.31
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Self-esteem and Relationship with Parents with Academic Procrastination in Students: An Analytical, Cross-Sectional Study

Abstract: Background & Aims: Procrastination is a very common phenomenon and almost a global problem that exists in all cultures. Studies show that (80-95%) of students are involved in some form of procrastination and (50%) of them are always procrastinating in doing homework and learning subjects. Academic procrastination is one of the factors affecting students' academic achievement and many students cannot use their maximum existential capacity due to this problem. In fact, procrastination causes a high degree of anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The results of this study indicated a significant negative relationship between students’ academic procrastination and self-esteem. Similarly, self-esteem is reportedly one of the factors affecting students’ academic procrastination in various studies [ 10 , 16 – 18 ]. In this respect, lower degrees of academic procrastination were observed in students with higher self-esteem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of this study indicated a significant negative relationship between students’ academic procrastination and self-esteem. Similarly, self-esteem is reportedly one of the factors affecting students’ academic procrastination in various studies [ 10 , 16 – 18 ]. In this respect, lower degrees of academic procrastination were observed in students with higher self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, students with low self-esteem often experience high levels of academic procrastination due to the fear of failure in achieving their goals. In fact, when students do not expect success and growth because of low self-esteem, they do not strive to achieve their goals [ 18 ]. Therefore, low self-esteem will result in students’ academic procrastination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations